2008
DOI: 10.4319/lo.2008.53.6.2503
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the initiation of blooms of the raphidophyte Heterosigma akashiwo and the diatom Skeletonema costatum in a port in Japan

Abstract: We investigated how environmental factors initiate Heterosigma akashiwo and Skeletonema costatum blooms from resting stages in bottom sediments in a shallow port over 2 yr. Using field-collected sediments, we also conducted laboratory experiments on how light intensity affects germination of resting stages and growth of the germinated cells. Both phytoplankton species bloomed only in summer, when water temperature and solar radiation were high enough for growth. All three blooms of H. akashiwo and the earliest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 39 publications
2
62
0
1
Order By: Relevance
“…In addition to the traditional concept of allelopathy between phytoplankton species, APPCs produced by H. akashiwo may have another role. Shikata et al (2008) reported that the density of H. akashiwo cysts in the bottom sediment of the Hakozaki Fishing Port sharply increased from the time of the peak to the decline phase of a bloom in the water. Thus, APPCs may not only contribute to growth competition with other species during the late exponential phase of the bloom as reported by Pratt (1966), Honjo et al (1978), and Honjo and Tabata (1985), but also contribute to maintenance of monospecific H. akashiwo blooms through inhibitory effects on competitors.…”
Section: Final Conclusionmentioning
confidence: 99%
“…In addition to the traditional concept of allelopathy between phytoplankton species, APPCs produced by H. akashiwo may have another role. Shikata et al (2008) reported that the density of H. akashiwo cysts in the bottom sediment of the Hakozaki Fishing Port sharply increased from the time of the peak to the decline phase of a bloom in the water. Thus, APPCs may not only contribute to growth competition with other species during the late exponential phase of the bloom as reported by Pratt (1966), Honjo et al (1978), and Honjo and Tabata (1985), but also contribute to maintenance of monospecific H. akashiwo blooms through inhibitory effects on competitors.…”
Section: Final Conclusionmentioning
confidence: 99%
“…The southeastern area of the bay is closed off by a large breakwater. Our investigation was conducted in Hakozaki Fishing Port (33°37′30′′N, 130°25′90′′E; Shikata et al 2008; water depth 2.5-4.5 m), which is located inside the breakwater in the southeastern area of the bay.…”
Section: Field Studymentioning
confidence: 99%
“…Hakata Bay, Japan, is a small, shallow bay (Shikata et al, 2008; east-west 20 km, north-south 10 km; maximum depth 23 m; tidal range 2 m). The southeastern area of the bay is closed off by a large breakwater.…”
Section: Field Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in estuarine primary production has been linked to the increase in water turbidity promoted by dredging (EWA-OBOHO et al, 2008) and differential sediment transport (CHEN et al, 2005). Resuspension of bottom sediments can also bring phytoplankton resting stages to the water column as vegetative cells (SHIKATA et al, 2008), leading to the development of blooms that may include red tide species (ANDERSON et al, 1983). Input of nutrient loads (CONLEY, 2000;DE JONGE et.…”
Section: Introductionmentioning
confidence: 99%